(untitled) (LACCEI, 2024)
The main objective of the research is to propose maintenance management based on reliability to reduce failures of the machinery of the broiler line of a poultry company. For this reason, maintenance management techniques were applied: criticality analysis of machines or processes, fault tree, mode effect analysis and failures (AMEF). For this reason, the objective of this thesis was to develop a preventive maintenance management plan based on Reliability (RCM), which yielded the following results: failures were reduced by 66%, as a result, availability increased from 86% to 96%, in the AMEF the NPR decreased by 65% ​​with the application of the maintenance strategies proposed for each potential failure mode, the implementation of the reliability-based maintenance management plan resulted in annual savings of 75,799.17 soles due to the reduction of machinery failures.